The Journey of Maguindanaon Students in Learning Arabic and English Languages - BALAYANAN, ACREMAH; Lumbu-an, Jenevieve (Studies in Technology and Education, 2025)
This study explores the experiences of Maguindanaon students at Pimbalayan National High School in achieving balanced proficiency in Arabic and English during the 2024–2025 academic year. The purpose is to understand how these students navigate the dual demands of religious and secular education through bilingual acquisition. The research addresses the problem of limited integration between faith-based and academic instruction, which poses challenges to students' linguistic development and cultural preservation. Using a transcendental phenomenological approach guided by Moustakas’ (1994) framework, data were collected through in-depth interviews and focus group discussions. Participants were selected based on defined inclusion and exclusion criteria to ensure diverse and representative perspectives. Findings reveal that despite encountering linguistic barriers, financial hardships, and limited educational resources, students demonstrate resilience supported by family, community, and institutional structures. Their bilingual proficiency fosters aspirations in both religious and professional fields, highlighting language as a bridge between identity and future goals. The study concludes that a supportive, inclusive, and culturally responsive learning environment enhances both academic performance and personal development. Its significance lies in informing educational policies and practices aimed at strengthening bilingual education for marginalized communities, ultimately promoting equity, inclusion, and empowerment through language.